Developing a new mobile network ownership model using a risk allocation framework. (5th July 2021) - Kim, Dongwook; Zo, Hangjung; Lee, Junghwan
Mobile communications and broadband have become more prominent in driving the global economic growth. However, the next generation networks are increasing the cost burden of the industry. In this context, the mobile industry needs to rethink the traditional ownership model and consider mixed ownership. This study consolidates the theories of public private partnership and extend them to general partnerships to deduce recommendations for the partnerships. The risk allocation framework for partnership theories is used in the analysis and case studies are complemented whenever possible to corroborate the conclusions. Based on the findings, the partnership should be established such that the party that can best mitigate/resolve the risk bears the risk. The technology development should focus on interoperability of network components especially in the radio access and optimising the cost of end nodes. Finally, regulatory approaches should be centralised and avoid opportunistic behaviour to maximise trust in the partnership.